Holiday Trips: Convenience, Efficiency and Effectiveness - Liasidou, Sotiroula (My University, 2014)
This paper aims to provide an understanding on the decision making process that guide tourism trips based on the various strategies developed by the airlines. The primary research data was analysed using factor analysis as a pertinent statistical tool for grouping variables in order to understand common consumption behaviours. The results of the study are indicative and suggest that tourists are classified in accordance with 'customer service' that include ground and in-flight service. Then, the second factor is 'price sensitive and Internet', which refers to dimensions such as the airline ticket and the frequency of trips. Finally, 'selection in travel behaviour' is associated with the choice based on the operation of the airlines, for instance the airports.
Keywords: Airports; Airlines; Consumer behaviour; Factor analysis; Cyprus